Silicon and Nitrate Differentially Modulate the Symbiotic Performances of Healthy and Virus-Infected Bradyrhizobium-nodulated Cowpea (Vigna unguiculata), Yardlong Bean (V. unguiculata subsp. sesquipedalis) and Mung Bean (V. radiata) - Izaguirre-Mayoral, Maria Luisa (Plants (Basel), 2017)
The effects of 2 mM silicon (Si) and 10 mM KNO(3) (N)—prime signals for plant resistance to pathogens—were analyzed in healthy and Cowpea chlorotic mottle virus (CCMV) or Cowpea mild mottle virus (CMMV)-infected Bradyrhizobium-nodulated cowpea, yardlong bean and mung bean plants. In healthy plants of the three Vigna taxa, nodulation and growth were promoted in the order of Si + N > N > Si > controls. In the case of healthy cowpea and yardlong bean, the addition of Si and N decreased ureide and α-amino acids (AA) contents in the nodules and leaves in the order of Si + N> N > Si > controls. On the other hand, the addition of N arrested the deleterious effects of CCMV or CMMV infections on growth and nodulation in the three Vigna taxa. However, the addition of Si or Si + N hindered growth and nodulation in the CCMV- or CMMV-infected cowpea and yardlong bean, causing a massive accumulation of ureides in the leaves and nodules. Nevertheless, the AA content in leaves and nodules of CCMV- or CMMV-infected cowpea and yardlong bean was promoted by Si but reduced to minimum by Si + N. These results contrasted to the counteracting effects of Si or Si + N in the CCMV- and CMMV-infected mung bean via enhanced growth, nodulation and levels of ureide and AA in the leaves and nodules. Together, these observations suggest the fertilization with Si + N exclusively in virus-free cowpea and yardlong bean crops. However, Si + N fertilization must be encouraged in virus-endangered mung bean crops to enhance growth, nodulation and N-metabolism. It is noteworthy to see the enhanced nodulation of the three Vigna taxa in the presence of 10 mM KNO(3).